Anatomical predictors of conduction damage after transcatheter implantation of the aortic valve. Issue 1 (9th April 2019) - Tretter, Justin T; Mori, Shumpei; Anderson, Robert H; Taylor, Michael D; Ollberding, Nicholas; Truong, Vien; Choo, Joseph; Kereiakes, Dean; Mazur, Wojciech
Abstract : Objective: Conduction damage following transcatheter aortic valve implantation (TAVI) remains common. Anatomical risk factors remain elusive. We assessed the impact of variability in the dimensions of the membranous septum and position of the aortic root on the occurrence of conduction damage following TAVI. Methods: The dimensions of the membranous septum, the rotational position of the aortic root correlating to variability in the central fibrous body width, and wedging of the aortic root were assessed on pre-TAVI CT datasets. The depth of implantation was measured from the final aortic angiogram. The variables were compared with the occurrence of both permanent pacemaker insertion (PPI) and left bundle branch block (LBBB) following TAVI. Results: Of 200 patients who met inclusion criteria (mean age = 81 years ± 7.7, 49% men), 20.5 % underwent PPI after TAVI. New LBBB occurred in 23.5%, 21.3 % of whom required PPI. Preprocedural right bundle branch block (OR = 7.00; CI 3.13 to 15.64), valve type (OR=2.35; CI 1.13 to 4.87), depth of implantation (OR=1.62; CI 1.01 to 2.61) and the difference between depth of implantation and the distance from the virtual basal ring to the inferior margin of the membranous septum (OR=0.61; CI 0.38 to 0.99) were all associated with PPI, with similar associations with LBBB. No gross anatomical variable alone was associated with conduction damage. Conclusions: Gross anatomical variation of the aortic root and its underlying support, including the membranous septum, were not associated with the occurrence of either PPI or new LBBB. Procedural characteristics associated with these adverse outcomes suggest that the depth of implantation and radial force of the bioprosthesis, regardless of gross anatomical variability, increase the risk for conduction damage.